Health Education Programs to Improve Foot Care Behavior and Reduce Stress Levels among People with Type 2 Diabetes: A Systematic Review - Yusuf, Ah.; Dewi, Sanda Prima; Yunitasari, Esti (International Journal of Psychosocial Rehabilitation, 2020)
The complications of diabetes among people are a major health concern. Foot problems such as neuropathy, ulcer and ultimately amputation are a great burden on people with diabetes. Diabetes foot education programs can influence the behavior of people in practicing foot care behavior and controlling their stress levels. However, the educational approaches used by educators are varied. Therefore, it is important to assess the education programs from various evidence-based practices. This systematic review aims to assess the health education programs to improve foot care behavior and reduce stress levels among people with type 2 diabetes. We searched six databases: EBSCOhost medical collections (MEDLINE, CINAHL, Psychology and Behavioral Sciences Collection), SAGE, Wiley Online Library, ScienceDirect, SpringerLink and Web of Science, for articles published from January 2013 to December 2018. The search was based on the inclusion criteria and keywords including ‘health’, ‘education’, ‘foot’, ‘care’, ‘stress’, and ‘diabetes’. Fourteen studies were assessed and reviewed in the final stage. The findings of this study support the claim that a health education programs increase foot care behavior scores and reduces stress levels. However, there were certain methodological concerns in the reviewed articles, indicating the need for further evaluation. In the future, researchers and practitioners must implement a vigorous education program focusing on diabetes foot care among the population.